2006
DOI: 10.1002/pmic.200500779
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crystallin family proteins in vitreous body in rat endotoxin‐induced uveitis: Involvement of crystallin truncation in uveitis pathogenesis

Abstract: Endotoxin-induced uveitis (EIU) is an animal model of acute ocular inflammation. To characterize the mechanism of EIU, we analyzed the infiltration of proteins in the vitreous bodies of rats with EIU and normal rats using 2-DE and micro LC/LC-MS/MS. Twenty spots were identified in vitreous bodies of rats. Eighteen of these spots were members of the crystallin family. The truncated form of beta A4- and beta B2-crystallin were predominant in normal vitreous bodies, but there were intact form of crystallins in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Crystallins are chaperone proteins expressed in many tissues[30,31], and were present in both the retina and vitreous. The top 20 retina proteins contained fifteen different crystallins, which are upregulated in the retina during the progression of ocular diseases, including uveitis[30,32,33]. Thus, multiple cells and tissues, including those outside the eye, may contribute to the vitreous proteome.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallins are chaperone proteins expressed in many tissues[30,31], and were present in both the retina and vitreous. The top 20 retina proteins contained fifteen different crystallins, which are upregulated in the retina during the progression of ocular diseases, including uveitis[30,32,33]. Thus, multiple cells and tissues, including those outside the eye, may contribute to the vitreous proteome.…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the mechanism of EIU, Bahk et al analysed the infiltration of proteins in the vitreous bodies of rats with EIU and normal rats using 2-DE-MALDI-TOF/MS and micro LC/LC-MS/MS, identifying specific modifications in the crystallin family proteins [50]. …”
Section: Future Perspectives: Proteomics For Intravitreal Inflammamentioning
confidence: 99%
“…In our previous studies, crystallins (the major proteins of the vitreous body) were induced in response to ocular inflammations of animal uveitis models. These findings suggested that post-translational truncations of αA- and αB-crystallins, phosphorylation of αB-crystallin, and new production of βA4- and βB2-crystallins are intercorrelated with uveitis progression and inflammatory responses [13,14]. The regulatory mechanism of the phosphorylation of αB-crystallin [29] results in the inhibition of RAS [23].…”
Section: Discussionmentioning
confidence: 99%
“…During ischemic preconditioning, the bovine B2 chain of α-crystallin is activated through the phosphorylation of the serine residues (Ser-45 and Ser-59) mediated by ERK1/2 and p38, respectively, thereby acting as an effector protein [8-12]. More recently, post-translational modifications of mouse αA-crystallin have been reported [13,14]. The N-terminal acetylation and the variable C-terminal truncation of αA-crystallin are regarded as important modifications for the activation of crystallin proteins [15].…”
mentioning
confidence: 99%